From Sacred Objects to Open Symbolic Text: Symbolic Consumption and the Contemporary Transformation of Chinese Religious Art—A Case Study of Dehua White Porcelain Statues of Gods and Buddhas - Chen Xing, Arkom Sangiamvibool (Journal of Daoist Studies, 2026)
The contemporary transformation of Chinese religious art is often interpreted through the frameworks of secularization, commodification, or the decline of religious authority. While these perspectives explain important aspects of modern cultural change, they provide only a partial account of how religious artworks continue to generate new meanings within contemporary consumer society. This article examines the transformation of Dehua white porcelain statues of gods and Buddhas as a representative case of Chinese religious art and asks how symbolic meanings are reconstructed under conditions of symbolic consumption. Drawing upon artistic semiotics and symbolic consumption theory, the study combines historical analysis, iconographic analysis, visual analysis, interviews, and case studies to investigate the historical continuity and contemporary reinterpretation of these sculptures. Rather than understanding their transformation as a linear process of desacralization, the findings suggest that sacred meanings are reconfigured within an expanding symbolic system in which artists, consumers, market institutions, and Chinese religious culture jointly participate in meaning construction. In this process, Dehua white porcelain statues of gods and Buddhas evolve from relatively stable sacred objects into open symbolic texts, capable of supporting multiple context-dependent interpretations while maintaining historical continuity. The article argues that symbolic consumption does not eliminate sacredness but redistributes interpretive agency across multiple cultural actors. Based on this case, it proposes that the concept of open symbolic text provides a more appropriate framework than the conventional secularization paradigm for explaining the contemporary transformation of Chinese religious art. The study therefore contributes to research on religious art, applied art, artistic semiotics, and craft-heritage studies by offering an analytical perspective that emphasizes symbolic reconfiguration rather than symbolic loss.